Near‐Real‐Time Analysis of the Ionospheric Response to the 15 January 2022 Hunga Tonga‐Hunga Ha'apai Volcanic Eruption. Issue 10 (18th October 2022) - Maletckii, B.; Astafyeva, E.
Abstract: We present a near‐real‐time (NRT) scenario of analysis of ionospheric response to the 15 January 2022 Hunga Tonga‐Hunga Ha'apai eruption by using Global Navigation Satellite Systems data in the near‐field (in the vicinity of the volcano), and in the far‐field (Japan, North America, and South America). We introduce a new method to determine instantaneous velocities using an interferometric approach and using the time derivative of the total electron content (TEC). Moreover, for the first time, we propose a novel method that automatically estimates the apparent propagation velocity of ionospheric disturbances from NRT travel‐time diagrams. By using our new methods, we analyzed the dynamics of co‐volcanic ionospheric disturbances generated by the Hunga‐Tonga eruption, and we estimated the first propagation velocity in the near‐field to be ∼800–950 m/s, subsequently decreasing to ∼600 m/s. Based on these values, we conclude that in the near‐field, we detect ionospheric signatures of acoustic waves. In the far field, the apparent velocity of ionospheric disturbances was estimated to be between 277 and 365 m/s, which corresponds to the propagation of the Lamb wave. It is important to note that our new methods can successfully perform at low spatial resolution networks and with 30‐s cadence data. Also, they enable NRT spatio‐temporal analysis of ionospheric TEC response to smaller‐amplitude events. Key Points: We suggest novel methods that detect and determine spatio‐temporal characteristics of ionospheric disturbances in near‐real‐time (NRT) We analyze large‐ and small‐amplitude ionosphere response to the Tonga eruption in near (<2, 000 km) and far‐field (∼10, 000 km) in NRT scenario The amplitude of the dTEC/dt response to the Tonga eruption is comparable to the 2011 Tohoku earthquake and the 28 October 2003 solar flare